Is e-cigarette use associated with coronary heart disease and myocardial infarction? Insights from the 2016 and 2017 National Health Interview Surveys - Konstantinos E Farsalinos; Riccardo Polosa; Fabio Cibella; Raymond Niaura (SAGE Publishing, 2019)
Background: This study analyzed the National Health Interview Surveys (NHIS) of 2016 ( n  = 33,028) and 2017 ( n  = 26,742) to examine whether e-cigarette use is consistently associated with myocardial infarction (MI) and coronary heart disease (CHD). Methods: Surveys were examined separately and pooled. Logistic regression analysis was used, with demographics, e-cigarette use, smoking and risk factors for CHD (hypertension, hypercholesterolemia, and diabetes) being independent variables. Former smokers were subclassified according to quit duration (⩽ 6 and > 6 years). Results: For MI, an association was observed with some days e-cigarette (but not daily) use in the 2017 survey (OR: 2.11, 95% CI: 1.14-3.88, p  = 0.017). No statistically significant association was observed in the pooled analysis (daily e-cigarette use: OR: 1.35, 95% CI: 0.80-2.27, p  = 0.267). For CHD, an association was observed with daily e-cigarette use in the 2016 survey (OR: 1.89, 95% CI: 1.01-3.53, p  = 0.047). From the pooled analysis, no association was found between any pattern of e-cigarette use and CHD. In single-year and pooled analysis, both MI and CHD were strongly associated with all patterns of smoking, hypertension, hypercholesterolemia, diabetes, and age. Conclusions: The pooled analysis of the 2016 and 2017 NHIS showed no association between e-cigarette use and MI or CHD. The associations between established risk factors, including smoking, and both conditions were remarkably consistent. The inconsistent associations observed in single-year surveys and the cross-sectional design of the NHIS cannot substantiate any link between e-cigarette use and an elevated risk for MI or CHD. Longitudinal studies are needed to explore the effects of e-cigarette use on cardiovascular disease.